2021
DOI: 10.31104/jsab.v5i2.248
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Tujuan penelitian ini adalah untuk mengetahui pengaruh Corporate Social Responsibility (CSR) terhadap minat beli ulang dengan brand image sebagai variable mediasi. Populasi pada penelitian ini ialah konsumen yang mengetahui program CSR dan pernah membeli produk dari PT Indofood Sukses Makmur Tbk setidaknya lebih dari 2 kali. Metode yang digunakan ada penelitian ini adalah pendekatan kuantitatif. Jumlah sampel sebanyak 100 responden. Analisis data yang digunakan adalah dengan menggunakan program SmartPLS. Varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…Next, companies that implement sustainable CSR programs will also strengthen the corporate image and repurchase interest in the company. This has been proven by research conducted (Sitanggang et al, 2021) that CSR has a significant and positive effect on the brand image and interest in repurchase the public. From this presentation, it is concluded that there are still many companies that do not understand the proper and sustainable implementation of CSR implementation.…”
Section: Concretementioning
confidence: 88%
“…Next, companies that implement sustainable CSR programs will also strengthen the corporate image and repurchase interest in the company. This has been proven by research conducted (Sitanggang et al, 2021) that CSR has a significant and positive effect on the brand image and interest in repurchase the public. From this presentation, it is concluded that there are still many companies that do not understand the proper and sustainable implementation of CSR implementation.…”
Section: Concretementioning
confidence: 88%